The Influence of Positive End-Expiratory Pressure on Surgical Field Conditions During Functional Endoscopic Sinus Surgery. (February 2015) - DeMaria, Samuel; Govindaraj, Satish; Huang, Alice; Hyman, Jaime; McCormick, Patrick; Lin, Hung Mo; Levine, Adam
Abstract : BACKGROUND: Functional endoscopic sinus surgery (FESS) is the mainstay of surgical treatment for sinonasal disease. This surgery carries certain risks. Most of these risks relate to the quality of the surgical field. Thus, mechanisms by which the surgical field can be improved are important to study. We sought to determine whether positive end-expiratory pressure (PEEP) had a deleterious effect on the quality of the surgical field in patients undergoing primary FESS. METHODS: Forty-seven patients were randomized to a ventilation strategy using either 5 cm H2 O of PEEP or zero added PEEP. The quality of the surgical field was measured every 15 minutes using a validated surgical scoring method. RESULTS: The addition of PEEP did not have any measurable effect on the surgical field scores after onset of surgery (odds ratio [OR] (95% confidence interval [CI]) = 1.06 (0.44–2.58), P = 0.895 for side 1; OR (95% CI) = 0.56 (0.16–1.93), P = 0.356 for side 2). The peak inspiratory pressure did have an effect on surgical grades. Every cm H2 O of added pressure over 15 cm H2 O total pressure contributing to increased odds of higher surgical field score. For each cm H2 O increase in inspiratory pressure above 15cm H2 O increased the surgical field score (OR [95% CI] 1.13 [1.04–1.22], P = 0.002). CONCLUSIONS: During FESS surgery if PEEP is added, it is important to keep the mean inspiratory pressure below 15cm H2 O to avoid worsening surgical field conditions. Abstract : Published ahead of print November 25, 2014.